Increased O-GlcNAcylation of Endothelial Nitric Oxide Synthase Compromises the Anti-contractile Properties of Perivascular Adipose Tissue in Metabolic Syndrome - da Costa, Rafael M.; Silva, Josiane F. da; Alves, Juliano V.; Dias, Thiago B.; Rassi, Diane M.; Garcia, Luis V.; Lobato, Núbia de Souza; Tostes, Rita C. (Frontiers in Physiology, 2018)
Under physiological conditions, the perivascular adipose tissue (PVAT) negatively modulates vascular contractility. This property is lost in experimental and human obesity and in the metabolic syndrome, indicating that changes in PVAT function may contribute to vascular dysfunction associated with increased body weight and hyperglycemia. The O-linked β-N-acetylglucosamine (O-GlcNAc) modification of proteins (O-GlcNAcylation) is a unique posttranslational process that integrates glucose metabolism with intracellular protein activity. Increased flux of glucose through the hexosamine biosynthetic pathway and the consequent increase in tissue-specific O-GlcNAc modification of proteins have been linked to multiple facets of vascular dysfunction in diabetes and other pathological conditions. We hypothesized that chronic consumption of glucose, a condition that progresses to metabolic syndrome, leads to increased O-GlcNAc modification of proteins in the PVAT, decreasing its anti-contractile effects. Therefore, the current study was devised to determine whether a high-sugar diet increases O-GlcNAcylation in the PVAT and how increased O-GlcNAc interferes with PVAT vasorelaxant function. To assess molecular mechanisms by which O-GlcNAc contributes to PVAT dysfunction, thoracic aortas surrounded by PVAT were isolated from Wistar rats fed either a control or high sugar diet, for 10 and 12 weeks. Rats chronically fed a high sugar diet exhibited metabolic syndrome features, displayed increased O-GlcNAcylated-protein in the PVAT and loss of PVAT anti-contractile effect. PVAT from high sugar diet-fed rats for 12 weeks exhibited decreased NO formation, reduced expression of endothelial nitric oxide synthase (eNOS) and increased O-GlcNAcylation of eNOS. High sugar diet also decreased OGA activity and increased superoxide anion generation in the PVAT. Visceral adipose tissue samples from hyperglycemic patients showed increased levels of O-GlcNAc-modified proteins, increased ROS generation and decreased OGA activity. These data indicate that O-GlcNAcylation contributes to metabolic syndrome-induced PVAT dysfunction and that O-GlcNAcylation of eNOS may be targeted in the development of novel therapies for vascular dysfunction in conditions associated with hyperglycemia.